Discovery Learning Model to Improve Collaborative Pancasila Student Profiles and Mathematics Learning Outcomes - Ramuni A (Syntax Corporation Indonesia, 2022)
This action research aims to improve the profile of collaborative Pancasila students and mathematics learning outcomes in class VIII students at Public Junior High School 5 Sanggau. This action research is a single class research. The implementation time starts from October 23 to November 8, 2021 which is divided into 4 meetings (pretest, treatment 1, treatment 2, posttest). The design used in this research is The One-Group Pretest-Posttes Design. This design was used in group research, namely class VIIIA which was given treatment in the form of applying the Discovery Learning of two-variable linear equation (PLDV) material. Based on the results of the analysis of the observation sheet, an increase of 25% was obtained where at the first 2 treatment meetings, 65% of students actively collaborated while in the treatment , 90% of students actively collaborated. Student learning outcomes showed an increase of 50%, where the results of the pretest showed 42.85% and the post was 92.85%. In addition, the results of data processing on the normality test showed that the pretest 0.197 > 0.05 meaning the data was normally distributed, the data homogeneity test showed sig 0.108 > 0.05 meaning the data was homogeneous and the T test showed a significance = 0.00 so it can be concluded that the hypothesis is accepted. means that there is an increase in the value of the pretest with the posttest.